KLASIFIKASI STRUKTUR PEMBENTUK DAN MAKNA KANYOUKU DALAM BUKU 101 JAPANESE IDIOMS KARANGAN SENKO K. MAYNARD - M. Qadafi Dasman; Nana Rahayu; Intan Suri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: Idioms in Japanese are called kanyouku. Kanyouku is an expression that is formed from a combination of two or more words, where the meaning of each of the forming words cannot be interpreted by just looking at the sentence (Shinmura, 2018). Kanyouku can be divided based on the forming structure and its meaning. This research aims toexplain classification kanyouku based on the forming structure and meaning in the book 101 Japanese idioms: Understanding Japanese Language andCulture Through Popular Phrases essay Senko K. Maynard. The theory used in this research is classification kanyouku based on forming structures according to Miharu (2022) and based on meaning according to Muneo (1992). This research is a qualitative descriptive study. From the results of the analysis of 25 kanyouku, there are 10 doushi kanyouku, 5 keiyoushi kanyouku and 10 meishi kanyouku. Based on the meaning,consists of 2 kankaku, kanjou wo arawasu kanyouku, 9 karada, seikaku, taido wo arawasu kanyouku, 2 koui, dousa, koudo arawasu kanyouku, 10 joutai, teido, kachi wo arawasu kanyouku and 2 shakai, seikatsu, bunka wo arawasu kanyouku.Keywords: Kanyouku, Idioms, Classification.